ANALISIS FORMAL KARYA LUKISAN IDA BAGUS KETUT SUTA - Made Satya Hariwarman; I Gusti Ngurah Sura Ardana; Luh Suartini (Jurnal Pendidikan Seni Rupa Undiksha, 2022)
This study aims to describe (1) Identify the characteristics of Ida Bagus Ketut Suta painting (2) Describe the theme of Ida Bagus Ketut Suta's painting (3) Describe the visual form of Ida Bagus Ketut Suta's painting using formal analysis methods. The subject and object of this research is the profile of Ida Bagus Ketut Suta with traditional paintings that have been made by Ida Bagus Ketut Suta. This research is a qualitative descriptive study, data collection in this study used the techniques of (1) observation, (2) interviews, (3) documentation, and (4) literature. The results of this study indicate that (1) The results of the visual identification mapping of Ida Bagus Ketut Suta's traditional paintings based on a comparison of several types of traditional wayang paintings in Bali, show that the results of his paintings have different characteristics from traditional paintings that developed in eastern Bali but are the result of the development of traditional paintings from Tabanan, namely the wayang kopang style painting, (2) The themes of several paintings that have been made by Ida Bagus Ketut Suta can be identified through formal analysis methods that are based on folklore Hindu, (3) formal visual analysis of forms from Ida Bagus Ketut Suta's painting, which is a form of wayang tradition painting that has its own characteristic and varied appearance.Keywords: traditional painting, Ida Bagus Ketut Suta